(untitled) (Fiep Bulletin - online, 2014)
Bilateral asymmetries in force magnitude are frequently found in lower limbs. The aim in this study was the identification of lateral asymmetries in LL of futsal players by motor test. Thirteen futsal players of the juniors category participated of this study. They performed the velocity/agility test. Bilateral asymmetries were identificated if the bilateral difference was greater than 15%. Lateral asymmetries significance don’t was found between motor velocity with direction change, but the subjects showed greatest velocity with direction change for right. Future studies with a larger sample and with different ages are necessary to the applicability of the results is sustained scientifically.